Geming xiandai jingqu "Ziqu wei Hushan" Zhongguo renmin jiefangjun zhencha paizhang Yang Zirong
'Modern Revolutionary Peking Opera "Taking Tiger Mountain by Strategy" Chinese Liberation Army reconnaissance platoon leader Yang Zirong'. Printno. 8.3.11.